2012
DOI: 10.1103/physreva.86.062331
|View full text |Cite
|
Sign up to set email alerts
|

Robust adaptive measurement scheme for qubit-state preparation

Abstract: In this paper, the method of adaptive measurement for qubit-state preparation developed by Jacobs is reconsidered, and an alternative scheme that works even under unknown unitary evolution of the state is shown.The key idea is that the measurement is adaptively changed so that one of the eigenstates of the measured observable is always set between the current and the target states while that eigenstate converges to the target. The most significant feature of this scheme is that the measurement strength can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Measurement-only manipulation has been demonstrated using a fixed measurement basis [15], but unlike Hamiltonian-based methods, implementation of a timedependent measurement basis is lacking. Such a capability is a versatile additional degree of freedom for measurement based protocols, such as rapid state purification [5] and state manipulation [9,10,16], for control by projection into a subspace referred to as quantum Zeno dynamics [17], and for measurement-based quantum computation [18].In this Letter, we present a method to dynamically tune the measurement operator in a circuit-QED system, and use this capability to deterministically and incoherently manipulate the state of an effective qubit. Our method relies on the suppression of coherent evolution via strong measurement, known as the quantum Zeno effect (QZE), which has been observed in many systems [19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement-only manipulation has been demonstrated using a fixed measurement basis [15], but unlike Hamiltonian-based methods, implementation of a timedependent measurement basis is lacking. Such a capability is a versatile additional degree of freedom for measurement based protocols, such as rapid state purification [5] and state manipulation [9,10,16], for control by projection into a subspace referred to as quantum Zeno dynamics [17], and for measurement-based quantum computation [18].In this Letter, we present a method to dynamically tune the measurement operator in a circuit-QED system, and use this capability to deterministically and incoherently manipulate the state of an effective qubit. Our method relies on the suppression of coherent evolution via strong measurement, known as the quantum Zeno effect (QZE), which has been observed in many systems [19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…Measurement-only manipulation has been demonstrated using a fixed measurement basis [15], but unlike Hamiltonian-based methods, implementation of a timedependent measurement basis is lacking. Such a capability is a versatile additional degree of freedom for measurement based protocols, such as rapid state purification [5] and state manipulation [9,10,16], for control by projection into a subspace referred to as quantum Zeno dynamics [17], and for measurement-based quantum computation [18].…”
mentioning
confidence: 99%
“…where J is the inter-well tunnelling and U is the collisional interaction strength ( figure 3(a)). The standard strategies of unitary control [5,6] or control-free engineering [11,12,[14][15][16][17] require modifications in this setting: changing the Hamiltonian parameters abruptly, as for bang-bang control or the SU(2)-decomposition, compromises the lowest-band approximation due to vibrational excitations [9]. Continuous changes impose a speed-limit on achievable operations [7].…”
Section: Fock-state Generationmentioning
confidence: 99%
“…Besides unitary control via the system Hamiltonian, quantum state engineering can also be exerted for a fixed Hamiltonian via the back-action induced by measurements [11][12][13][14][15][16][17][18]. On the one hand, measurement operators that are adapted on previous measurement outcomes can steer a quantum state into a target state [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The continuous measurement is again useful to solve the problem, because it continuously reduces the entropy of the system; furthermore, to overcome the issue that any measurement induces a probabilistic (i.e. non-deterministic) behavior of the system, we employ the adaptive measurement technique [34,35], which is a kind of feedback control that changes the measured observable continuously in time, depending on the past measurement results. It will be actually demonstrated that, in some examples, this method realizes the deterministic stabilization of the target state.…”
Section: Introductionmentioning
confidence: 99%